Análise de metodologias para avaliação da eficiência energética de edificações públicas - Géssica Mara Rodrigues (2020)
In 2009, the Brazilian labeling program of buildings, PBE Edifica, was launched, which indicates technical requirements and methods of classification of building energy efficiency. In these more than 10 years of validity, works were developed applying the Regulation for Commercial, Service and Public Buildings (RTQ-C) and limitations were verified that showed the need to improve the method. Therefore, a new evaluation proposal was prepared, still under analysis, named as Inmetro Normative Instruction for Commercial, Services and Public Buildings (INI-C). This study aims to analyze the feasibility of this new proposal to understand the whole process and compare the changes in the evaluation methods. The methodology is divided into five main stages. The first stage is an initial analysis of the energy efficiency assessment method in buildings present in RTQ-C and INI-C. In the second stage there is a determination of case study. The third and fourth consist of the application of the RTQ-C and INI-C prescriptive methods, respectively, for the building defined as a case study. The fifth stage presents an analysis of the evaluation process and a survey of the time spent, in addition to the comparison of the electricity consumption estimated through the INI-C with the actual consumption of the analyzed building. As a result, the envelope system showed the greatest changes between the methods, establishing less generalized parameters on the analyzed building, and brought solutions to most of the limitations pointed out in the current method. The introduction of the evaluation of the natural conditioning system in the simplified method requires more analysis, since the metamodel used to prove the PHOCT has little scope for solutions. The lighting system showed a different level of efficiency between the methodologies, with the analysis of requirements only for level A at INI-C being the main factor for this change. As a result, the final classification of the Building CAD1 - UFMG had different levels between the evaluations. When comparing the consumption predicted by INI-C with the actual consumption, the value was overestimated by 3.7 times, which indicates the need to improve the reference data used.